Lignocellulosic agroindustrial waste in Peru: potential for bioethanol, energy, and reduction of CO2 emission - Retto-Hernandez, Patricia (2020)
ABSTRACT The residues from agricultural and agroindustrial activities are not adequately valorised and at best they are destined for animal consumption or else they are inadequately disposed of. The objective of the present work was to estimate and highlight the energy (calorific and electric) potential of second-generation bioethanol production using lignocellulosic waste from the most important crops in Peru. In addition, the reduction of CO2 emissions by using bioethanol produced from those lignocellulosic wastes was estimated. The biomass considered in this study was from the harvest and processing of sugarcane, rice, banana, yellow corn, oil palm and asparagus. It was determined that the annual lignocellulosic biomass availability was ~22 million tons, from which, 33.03% correspond to banana waste, 28.56% correspond to sugarcane waste. The potential of bioethanol production and energy generation was obtained using a theory conversion of cellulose, hemicellulose of each biomass. It was calculated 3.51 million tons of bioethanol/year, which total energy corresponds to 2.16 million toe/year with an electric energy potential of 8.81 GWh/year. This quantity could be enough to supply 9.11% and the total national energy demand and 0.02% of the electric energy demand, besides, it could help reduce in about 19.86% the CO2 emissions.